2016
DOI: 10.1002/ab.21676
|View full text |Cite
|
Sign up to set email alerts
|

An ERP study on hostile attribution bias in aggressive and nonaggressive individuals

Abstract: Hostile attribution bias (e.g., tendency to interpret the intention of others as hostile in ambiguous social contexts) has been associated with impulsive aggression in adults, but the results are mixed and the complete sequence of hostile inferential processes leading to aggression has not been investigated yet. The goal of this event-related brain potentials (ERPs) study was to track the neural activity associated with the violation of expectations about hostile versus nonhostile intentions in aggressive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
(73 reference statements)
1
16
0
3
Order By: Relevance
“…A recent study brought partial support to this model by showing that perceived social rejection vs. inclusion had a significant effect on RPI performance as a function of the participants’ frequency of use of splitting [85]. Other studies supported the existence of the model’s implicit and emotional pathway, by showing an association between an implicit measure of the BPD self-concept with a projective instrument and BDP impulsivity [86], as well as an association between an implicit measure of hostile cognitions or concept of self with event-related potentials and aggression [87,88,89]. More studies are in need to verify this model and particularly if the BPD self-concept and splitting dimensions of personality can be specifically related to inhibition processes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study brought partial support to this model by showing that perceived social rejection vs. inclusion had a significant effect on RPI performance as a function of the participants’ frequency of use of splitting [85]. Other studies supported the existence of the model’s implicit and emotional pathway, by showing an association between an implicit measure of the BPD self-concept with a projective instrument and BDP impulsivity [86], as well as an association between an implicit measure of hostile cognitions or concept of self with event-related potentials and aggression [87,88,89]. More studies are in need to verify this model and particularly if the BPD self-concept and splitting dimensions of personality can be specifically related to inhibition processes.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results demonstrate the need for further work investigating the cognitive mechanisms which underlie both attention and interpretation processes. For instance, Gagnon and colleagues have assessed the neural correlates of interpretation bias in aggression (Gagnon et al, 2016;Gagnon et al, 2017). They found that across both aggressive and non-aggressive samples, during a sentence completion task, participants showed increased N400 amplitude in response to non-hostile target words that violated the expectations of hostile scenarios.…”
Section: Future Researchmentioning
confidence: 99%
“…At the level of interpretation, the task could be an adaption of the "Hostile Expectancy Violation Paradigm" [126,127], which involves a written scenario containing initial sentences that are used to establish a hostile versus non-hostile context, during which a character simultaneously commits an ambiguous behavior directed at the reader. These sentences are then followed with a third sentence that ends with a word informing the reader of the nature of the character's underlying intention for his or her behavior.…”
Section: Adaptation Of Ict Applied To Impulsive Aggressionmentioning
confidence: 99%